Double Meander Dipole Antenna Array with Enhanced Bandwidth and Gain. (12th November 2021) - Awl, Halgurd N.; Mahmud, Rashad H.; Karim, Bakhtiar A.; Abdulkarim, Yadgar I.; Karaaslan, Muharrem; Deng, Lianwen; Luo, Heng
Abstract : In this paper, a new design of high gain and wide bandwidth microstrip patch antenna array containing double meander dipole structure is proposed. Two in-phase resonant frequencies in the Ku-band (12–18 GHz) could be achieved in the double meander dipole array structure, which lead to enhance impedance bandwidth without costing extra design section. Besides, further enhanced gain of 2 dBi of the array over the entire operating frequency range has been achieved by introducing a double-layer substrate technique. The proposed antenna has been fabricated using the E33 model LPKF prototyping PCB machine. The measurement results have been performed, and they are in very good agreement with the simulation results. The measured –10 dB impedance bandwidth indicates that the array provides a very wide bandwidth which is around 30% at the center frequency of 15.5 GHz. A stable gain with a peak value of 10 dBi is achieved over the operating frequency range. The E- and H-plane radiation patterns are simulated, and a very low sidelobe level is predicted. The proposed antenna is simple and has relatively low-profile, and it could be a good candidate for millimeter wave communications.